Peran Bahasa Indonesia dalam Bahasa Inggris - Wahid Nur Muhammad Firdaus; Malik Al Jabar; Ridho Noviansyah; Alfariq Reyhan Wisanggeni; Abednego Wahyu Purnama; Bayu Purbha Sakti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Language plays a fundamental role in human life, particularly in education and global communication. Indonesian serves as a national language and a unifying tool, while English functions as an international medium of global communication. This article aims to examine the role of the Indonesian language within the context of English learning and use, both as a linguistic aid and as a reinforcement of national identity. The research method applied is a literature review, analyzing various relevant academic sources. The findings indicate that Indonesian serves as a linguistic mediator, a competence indicator, and a conceptual framework in English learning. Proper use of Indonesian in English learning enhances students’ understanding of structure, meaning, and communicative context. In conclusion, the synergy between Indonesian and English should be developed in national education to build global literacy while preserving national linguistic identity.